Composite cross-linked structure for treating osteoarthritis and application thereof

By developing an injectable composite crosslinking structure, using chemical crosslinking technology of oxidized dextran and chondroitin sulfate, the problem of difficult drug concentration and serious side effects in the treatment of osteoarthritis has been solved, and the bone rupture has been significantly reduced The effect of cell production and joint swelling is effective in treating osteoarthritis.

CN119454748APending Publication Date: 2025-02-18LONGHUA HOSPITAL SHANGHAI UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310998823.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing treatment methods for osteoarthritis have problems with difficulty in reaching the ideal level of drug concentration, serious side effects, and an increased risk of knee replacement.

Method used

An injectable composite crosslinking structure was developed, formed by chemical crosslinking by oxidized dextran and chondroitin sulfate, with good self-healing ability and excellent rheology, and can be directly injected into the joint cavity.

Benefits of technology

It significantly reduces osteoclast production, reduces swelling of the knee joint cavity, reduces OARSI score, synovial area and cartilage defects in osteoarthritis mice, and effectively treats osteoarthritis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004385657020000151
    Figure BDA0004385657020000151
  • Figure HDA0004385657030000011
    Figure HDA0004385657030000011
  • Figure HDA0004385657030000012
    Figure HDA0004385657030000012
Patent Text Reader

Abstract

The invention relates to a cross-linked structure for treating osteoarthritis as well as preparation and application of the cross-linked structure. Specifically, the invention provides an injectable composite cross-linked structure which is obtained by mixing and cross-linking an oxidized dextran solution and an ammoniated chondroitin sulfate solution, wherein the oxidation degree of the oxidized dextran is below 10%; the amino grafting rate in the ammoniated chondroitin sulfate is 40%-80%. The obtained cross-linked structure can be directly injected to an ideal position and released in a minimally invasive mode, the two cartilage nutritional ingredients are cross-linked, the retention time of the two cartilage nutritional ingredients is prolonged, the slow release effect is achieved, knee joint tissue damage and swelling of osteoarthritis mice can be relieved, and therefore the cross-linked structure can be used for treating osteoarthritis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the fields of material science and clinical medicine, and in particular, relates to an injectable composite cross-linked structure capable of preventing and / or treating osteoarthritis and its application in medicines and health products. Background Art

[0002] Osteoarthritis (OA) is one of the most common musculoskeletal diseases in the elderly, and its main pathological manifestation is the progressive loss of cartilage and subchondral bone. The main risk factors for OA include age, obesity and traumatic injury, which cause joint swelling, pain and inflammation. The current treatment of OA mainly focuses on drugs to relieve pain and inflammation, including taking some analgesics and non-steroidal anti-inflammatory drugs or intra-articular injections of steroid drugs. However, long-term use of these drugs often leads to side effects such as gastrointestinal ulcers and bleeding, heart attacks, kidney disease, diabetes and osteoporosis. In addition, the latest studies have shown that steroid drugs also increase the risk of knee replacement. At present, the exact pathogenesis of knee osteoarthritis (KOA) is still unclear, so finding targets for the prevention and treatment of KOA is a very hot research field.

[0003] The main treatments for OA include oral administration or direct injection into the joint. Oral administration is the most commonly used method, but it is difficult to achieve the ideal concentration of drugs in the local joint. Direct intra-articular injection of drugs can solve the disadvantage of low oral drug concentration, and only a very small amount of drugs is needed to achieve the desired pharmacological effect. Currently, many nanomaterial release systems have been used to solve these shortcomings. Intra-articular drug injection is an ideal choice for the treatment of local joint diseases.

[0004] Therefore, it is of great significance to develop a drug that has a simple preparation method, low cost and can effectively treat osteoarthritis. Summary of the invention

[0005] The purpose of the present invention is to provide a drug which has a simple preparation method, low cost and can effectively treat osteoarthritis and its medical use.

[0006] In a first aspect of the present invention, an injectable composite cross-linked structure is provided, wherein the cross-linked structure is obtained by mixing and cross-linking an oxidized dextran solution and an ammoniated chondroitin sulfate solution;

[0007] The oxidation degree of the oxidized dextran is below 10%; the amino grafting rate of the ammoniated chondroitin sulfate is 40%-80%.

[0008] In another preferred embodiment, the oxidation degree of the oxidized dextran is less than 10%, preferably 1%-8%, and more preferably 2%-5%.

[0009] In another preferred embodiment, the oxidation degree of the oxidized dextran refers to the degree to which the hydroxyl groups in the dextran molecules are oxidized to aldehyde groups, specifically refers to the molar fraction of the aldehyde groups in the oxidized dextran to the total hydroxyl groups in the original dextran.

[0010] In another preferred embodiment, the amino grafting rate of the ammoniated chondroitin sulfate is 40%-80%, preferably 50-75%.

[0011] In another preferred embodiment, the amino grafting rate in the aminated chondroitin sulfate refers to the molar fraction of the amino groups in the aminated chondroitin sulfate to the carboxyl groups in the original chondroitin sulfate.

[0012] In another preferred embodiment, in the oxidized dextran solution, the concentration of oxidized dextran is 1%-10% (w / v), preferably 2%-8% (w / v), more preferably 3%-5%, such as 3%, 4%, 5%.

[0013] In another preferred embodiment, in the ammoniated chondroitin sulfate solution, the concentration of ammoniated chondroitin sulfate is 1%-10% (w / v), preferably 2%-8% (w / v), more preferably 3%-5%, for example 3%, 4%, 5%.

[0014] In another preferred embodiment, the volume ratio of the oxidized dextran solution to the aminated chondroitin sulfate solution is 0.8-1.2:0.8-1.2, preferably 1:1.

[0015] In another preferred embodiment, the aminated chondroitin sulfate is chondroitin sulfate grafted with dihydrazide.

[0016] In another preferred embodiment, the dihydrazide is selected from the following group: adipic acid dihydrazide, oxalic acid dihydrazide, or a combination thereof.

[0017] In another preferred embodiment, the glucan is selected from the group consisting of dextran, β-glucan, or a combination thereof.

[0018] In another preferred embodiment, the molecular weight of the oxidized dextran is 4000-25000, preferably 5000-20000, more preferably 8000-14000.

[0019] In another preferred embodiment, the molecular weight of the aminated chondroitin sulfate is 4000-25000, preferably 5000-20000, more preferably 8000-14000.

[0020] In another preferred embodiment, the injectable composite cross-linked structure has one or more of the following characteristics:

[0021] 1) The pore size of the composite cross-linked structure is between 20-100 μm, preferably 20-80 μm;

[0022] 2) The gel time of the composite cross-linked structure is 5-60 min, preferably 10-50 min, more preferably 10-30 min;

[0023] 3) The expansion ratio of the composite cross-linked structure is 10-30%, preferably 12-28%, preferably 15-20%;

[0024] 4) The composite cross-linked structure can be injected through a syringe, wherein the needle of the syringe has a thickness of 26g and 3g;

[0025] 5) The composite cross-linked structure has self-repairing ability and can self-heal within 60 minutes (preferably within 30 minutes).

[0026] In another preferred embodiment, the aminated chondroitin sulfate is prepared by the following method, which comprises the following steps:

[0027] a) mixing chondroitin sulfate and dihydrazide in water, wherein the mass ratio of chondroitin sulfate to dihydrazide is 1:2-10, preferably 1:2-5;

[0028] b) adjusting the pH to 3-6, mixing the mixed solution obtained in step a) with an activator to react;

[0029] c) adjusting the pH of the reaction solution obtained in step b) to 5-8 and then quenching; wherein quenching means placing the reaction solution in an ice bath at 0-5°C within 5 minutes and leaving it for 5-10 hours;

[0030] d) obtaining the aminated chondroitin sulfate by post-dialysis treatment.

[0031] In another preferred embodiment, in step a), the molecular weight of the chondroitin sulfate is 50-100 kDa.

[0032] In another preferred embodiment, in step a), the concentration of chondroitin sulfate in water is 0.5-50 g / L, preferably 2-10 g / L, such as 5 g / L.

[0033] In another preferred embodiment, in step b), the pH is adjusted to 4-5, preferably 4.5.

[0034] In another preferred embodiment, in step b), the activating agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) and N-hydroxysuccinimide (NHS).

[0035] In another preferred embodiment, the molar ratio of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (EDC) to N-hydroxysuccinimide (NHS) is 1-2:1-2, preferably 1-1.5:1-1.5, for example 1:1.

[0036] In another preferred embodiment, the mass ratio of the activator to chondroitin sulfate is 0.5-5:10, preferably 1-5:10.

[0037] In another preferred embodiment, in step b), the reaction time is 2-6 hours, preferably 4 hours.

[0038] In another preferred embodiment, in step c), the pH of the reaction solution obtained in step b) is adjusted to 6-8, preferably 7.

[0039] In another preferred embodiment, in step c), the quenching refers to placing in an ice bath at 0-3°C within 2 minutes and leaving for 6-10 hours.

[0040] In another preferred embodiment, in step d), the molecular weight cut-off of the dialysis is 8000-14000.

[0041] In another preferred embodiment, in step d), the dialysis time is 2-5 days, preferably 3 days.

[0042] In another preferred embodiment, step d) further includes a freeze-drying post-treatment step.

[0043] In another preferred embodiment, the oxidized dextran is prepared by the following method, which comprises the following steps:

[0044] i) mixing dextran and an oxidant in water and reacting them in the dark, wherein the ratio of the dextran to the oxidant is 10-20 mol sugar unit: 1 mol, preferably 12-18 mol sugar unit: 1 mol;

[0045] ii) adding diethylene glycol to terminate the reaction;

[0046] iii) After dialysis, oxidized dextran is obtained.

[0047] In another preferred embodiment, in step i), the oxidant is selected from the group consisting of sodium periodate, sodium perchlorate, potassium periodate, or a combination thereof.

[0048] In another preferred embodiment, in step i), the molecular weight of the dextran is 500-1000 kDa.

[0049] In another preferred embodiment, in step i), the concentration of the dextran in water is 5-20 g / L, preferably 5-10 g / L.

[0050] In another preferred embodiment, in step i), the oxidant is added in the form of a solution pre-dispersed in water, wherein the concentration of the oxidant solution is 1-5 g / L.

[0051] In another preferred embodiment, in step i), the reaction is carried out at 10-40° C. in the dark for 8-24 h, preferably 12 h.

[0052] In another preferred embodiment, in step ii), the mass ratio of diethylene glycol to the oxidant is 1:2-5.

[0053] In another preferred embodiment, in step iii), the dialysate is ultrapure water.

[0054] In another preferred embodiment, in step iii), the molecular weight cut-off of the dialysis is 8000-14000.

[0055] In another preferred embodiment, step iii) further includes a freeze-drying post-treatment step.

[0056] In another preferred embodiment, the injectable composite cross-linked structure is prepared by the following method, which comprises the steps of:

[0057] (a) providing the oxidized dextran solution and the aminated chondroitin sulfate solution;

[0058] (b) mixing the oxidized dextran solution and the aminated chondroitin sulfate solution to obtain a composite cross-linked structure.

[0059] In another preferred embodiment, the method is as described in the second aspect of the present invention.

[0060] In a second aspect of the present invention, there is provided a method for preparing an injectable composite cross-linked structure as described in the first aspect of the present invention, comprising the steps of:

[0061] (a) providing the oxidized dextran solution and the aminated chondroitin sulfate solution;

[0062] (b) mixing the oxidized dextran solution and the aminated chondroitin sulfate solution to obtain a composite cross-linked structure.

[0063] In another preferred embodiment, the oxidized dextran and the aminated chondroitin sulfate are independently as described in the first aspect of the present invention.

[0064] In another preferred embodiment, in the oxidized dextran solution, the concentration of oxidized dextran is 1%-10% (w / v), preferably 2%-8% (w / v), more preferably 3%-5%, such as 3%, 4%, 5%.

[0065] In another preferred embodiment, in the ammoniated chondroitin sulfate solution, the concentration of ammoniated chondroitin sulfate is 1%-10% (w / v), preferably 2%-8% (w / v), more preferably 3%-5%, for example 3%, 4%, 5%.

[0066] In another preferred embodiment, the solvent of the oxidized dextran solution and the aminated chondroitin sulfate solution is PBS buffer.

[0067] In another preferred embodiment, the volume ratio of the oxidized dextran solution to the aminated chondroitin sulfate solution is 0.8-1.2:0.8-1.2, preferably 1:1.

[0068] In a third aspect of the present invention, a cross-linked composition is provided, wherein the cross-linked composition is composed of the following components:

[0069] (a) an oxidized dextran solution; and (b) an ammoniated chondroitin sulfate solution,

[0070] The oxidation degree of the oxidized dextran is below 10%; the amino grafting rate of the ammoniated chondroitin sulfate is 40%-80%.

[0071] In another preferred embodiment, the volume ratio of the oxidized dextran solution to the aminated chondroitin sulfate solution is 0.8-1.2:0.8-1.2, preferably 1:1.

[0072] In another preferred embodiment, the oxidized dextran is as described in the first aspect of the present invention.

[0073] In another preferred embodiment, the aminated chondroitin sulfate is as described in the first aspect of the present invention.

[0074] In a fourth aspect of the present invention, there is provided use of the injectable composite cross-linked structure as described in the first aspect of the present invention in preparing a pharmaceutical composition for preventing and / or treating osteoarthritis.

[0075] In another preferred embodiment, the prevention and / or treatment of osteoarthritis includes one or more features selected from the following group:

[0076] 1) Reduce the synovial area of ​​the knee joint;

[0077] 2) reduce the area of ​​type X collagen-positive zone;

[0078] 3) Reduction of osteoclast count, preferably a 30% or greater reduction in osteoclast count within 12 weeks;

[0079] 4) Promote cartilage repair and increase cartilage area;

[0080] 5) Reduction of joint cavity volume, preferably a reduction of more than 25% in joint cavity volume within 12 weeks.

[0081] In a fifth aspect of the present invention, a composition or preparation is provided, comprising:

[0082] a) the injectable composite cross-linked structure according to the first aspect of the present invention or the cross-linked composition according to the third aspect of the present invention, and

[0083] b) a pharmaceutically and / or nutraceutically acceptable carrier.

[0084] In another preferred embodiment, the composition includes a pharmaceutical composition and a health care product composition.

[0085] In another preferred embodiment, the composition further comprises other drugs that can be used to prevent and / or treat osteoarthritis.

[0086] In another preferred embodiment, the dosage form of the composition includes powder, ointment, powder, injection, aqueous solution, enteric-coated sustained-release preparation or injection, preferably injection.

[0087] In the sixth aspect of the present invention, a method for preventing and / or treating osteoarthritis is provided, the method comprising the step of administering the cross-linked structure described in the first aspect of the present invention to a subject in need thereof.

[0088] In another preferred embodiment, the subject is a human or non-human mammal.

[0089] It should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described below (such as embodiments) can be combined with each other to form a new or preferred technical solution. Due to space limitations, they will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS

[0090] Figure 1 Shown is the process of the reaction between chondroitin sulfate (CS) and adipic acid dihydrazide (ADH) to generate CS-ADH (a); and the chemical structure of oxidized dextran (Odex) (b).

[0091] Figure 2 A schematic diagram of the mouse knee joint injection and gelation of the CS-Odex cross-linked structure is shown.

[0092] Figure 3 The NMR spectra of CS-ADH (a) and Odex (b) are shown.

[0093] Figure 4 Electron microscopy images of the cross-linked structures at different concentrations are shown.

[0094] Figure 5 The swelling ratio (a) and gel time (b) of the cross-linked structure of CS-Odex with different concentrations are shown.

[0095] Figure 6 Shows the rheological properties of the CS-Odex cross-linked structure; (a) strain amplitude sweep experiment, (b) strain experiment.

[0096] Figure 7 The actual gelation image (a) shows the cross-linked structure of CS-Odex; its injectability (b); and its self-healing ability (c).

[0097] Figure 8 The results of ultrasound examination of the mouse knee joint (a) and the changes in the volume of the mouse knee joint cavity (b) are shown, indicating that the CS-Odex cross-linking structure can reduce the volume of the knee joint cavity of KOA model mice.

[0098] Fig. 9 Shown are photographs of histological staining of paraffin sections of mouse knee joints.

[0099] Fig.10 The figure shows the changes of cartilage area (a), OARSI score (b), synovial area (c), expression of type X collagen (d), and number of osteoclasts (e) in the knee joints of mice. The arrows indicate the cartilage.

[0100] The results showed that the cross-linked structure of CS-Odex reduced the loss of articular cartilage in KOA, delayed the process of joint structure destruction, reduced the expression of type X collagen, and reduced osteoclast formation. DETAILED DESCRIPTION

[0101] Through extensive and in-depth research, the inventors have developed for the first time an injectable composite cross-linked structure formed by chemical cross-linking of chondroitin sulfate with a high degree of aminoation and dextran with a low degree of oxidation, which has regulated gel time and swelling ratio and has good self-healing ability.

[0102] The cross-linked structure obtained by mixing and cross-linking the two components of aminated chondroitin sulfate and oxidized dextran in the present invention can be directly injected into the joint cavity due to its excellent rheological properties and low viscosity, and directly plays the role of a "buffer" in the joint cavity; and the cross-linked structure can prolong its retention time and control the drug release in a minimally invasive manner.

[0103] After intra-articular injection, the cross-linked structure of the present invention can significantly reduce osteoclast formation (reduced by more than 45%), reduce knee joint cavity swelling (reduced by more than 30%), and reduce the OARSI score, synovial area and cartilage defect of osteoarthritis mice, thereby effectively treating osteoarthritis. On this basis, the inventors completed the present invention.

[0104] the term

[0105] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0106] As used herein, when used in reference to a specific recited numerical value, the term "about" means that the value may vary by no more than 1% from the recited value. For example, as used herein, the expression "about 100" includes all values ​​between 99 and 101 (e.g., 99.1, 99.2, 99.3, 99.4, etc.).

[0107] As used herein, the term "comprising" or "including (comprising)" may be open, semi-closed and closed. In other words, the term also includes "consisting essentially of" or "consisting of".

[0108] Chondroitin sulfate (CS)

[0109] Chondroitin sulfate is an anionic sulfonated glycosaminoglycan (linear polysaccharide) composed of a series of alternating disaccharide units (n-acetylgalactosamine and glucuronic acid). It is the main cartilage component of the human body, accounting for more than 80% of articular cartilage glycosaminoglycans. Clinical studies have shown that chondroitin sulfate is as effective as celecoxib in the treatment of KOA, reducing KOA cartilage volume defects and bone marrow lesions, reducing KOA joint swelling, and reducing joint effusion.

[0110] The current use of chondroitin sulfate has the following disadvantages: (1) Most CS are administered orally, and their bioavailability is low; (2) CS is water-soluble, which causes its rapid degradation, limiting its application as a biomaterial. Therefore, it is necessary to perform cross-linking or mixing with other polymers to improve its stability and achieve a sustained release effect.

[0111] In the present invention, chondroitin sulfate is aminated by reacting with adipic dihydrazide at both amino groups to obtain chondroitin sulfate-adipic dihydrazide (CS-ADH), which is then cross-linked with the oxidized dextran described below.

[0112] Dextran (Dex)

[0113] Glucan refers to a homopolysaccharide composed of glucose as a monosaccharide, with glucose units connected by glycosidic bonds. According to the type of glycosidic bonds, it can be divided into alpha-glucan and beta-glucan. Among alpha-glucans, dextran, also known as dextran, is the most studied and used.

[0114] Dextran, as a biocompatible, nontoxic, biodegradable hydrophilic polymer, has been widely used in medicine and biomedicine.

[0115] It is mainly composed of linear α-1,6 linked d-pyranose glucose residues, which are easily chemically oxidized by NaIO4 to obtain oxidized dextran with aldehyde groups. Oxidized dextran with aldehyde groups can react with the amine groups of chitosan, gelatin or their derivatives to form a series of cross-linked structures in situ.

[0116] In the present invention, dextran is reacted with a small amount of sodium periodate to obtain oxidized dextran (Oxidized Dextran, Odex).

[0117] Crosslinking composition

[0118] The invention provides a cross-linking composition for preventing and / or treating osteoarthritis, which consists of an oxidized dextran solution and an aminated chondroitin sulfate solution.

[0119] The aminated chondroitin sulfate is obtained by grafting chondroitin sulfate with adipic acid dihydrazide.

[0120] The oxidized dextran is obtained by oxidizing dextran under the action of sodium periodate.

[0121] The aminated chondroitin sulfate has a high degree of ammoniation, wherein the grafting rate of adipic acid dihydrazide is 40%-90%, preferably more than 50%, more preferably 55%-80%.

[0122] The oxidation degree of the oxidized dextran is low, wherein the aldehyde oxidation rate is below 10%, preferably below 5%.

[0123] Injectable composite cross-linked structure of the present invention

[0124] As used herein, the terms "injectable composite cross-linked structure of the present invention", "cross-linked structure of the present invention" and "CS-Odex cross-linked structure" are used interchangeably and refer to a cross-linked structure that can be injected into the joint cavity through a syringe by chemical cross-linking of chondroitin sulfate with a high degree of amination and dextran with a low degree of oxidation of the present invention.

[0125] The term "injectable" includes that the injectable composite cross-linked structure of the present invention is directly injected into the joint cavity via a syringe.

[0126] By utilizing the acylhydrazone and imine bonds obtained by the reaction of aminated chondroitin sulfate and oxidized dextran, the injectable composite cross-linked structure of the present invention can swell without dissolving in many solvents and water environments and has good self-healing ability.

[0127] The present invention chemically cross-links the two cartilage nutrients, ammoniated chondroitin sulfate and oxidized dextran, and directly injects them at an ideal position, thereby improving their bioavailability and delaying their respective degradation, thereby controlling drug release in a minimally invasive manner.

[0128] The injectable composite cross-linked structure of the present invention is obtained by mixing and cross-linking an oxidized dextran solution and an ammoniated chondroitin sulfate solution; wherein the oxidation degree of the oxidized dextran is below 10%; and the amino grafting rate of the ammoniated chondroitin sulfate is 40%-80%.

[0129] In another preferred embodiment, the oxidation degree of the oxidized dextran is less than 10%, preferably 1%-8%, more preferably 2%-5%. In another preferred embodiment, the amino grafting rate of the ammoniated chondroitin sulfate is 40%-80%, preferably 50-75%.

[0130] Preparation method of injectable composite cross-linked structure of the present invention

[0131] The injectable composite cross-linked structure is prepared by the following method, which comprises the steps of:

[0132] (a) providing the oxidized dextran solution and the aminated chondroitin sulfate solution;

[0133] (b) mixing the oxidized dextran solution and the aminated chondroitin sulfate solution to obtain a composite cross-linked structure.

[0134] In another preferred embodiment, the aminated chondroitin sulfate is prepared by the following method, which comprises the following steps:

[0135] a) mixing chondroitin sulfate and dihydrazide in water, wherein the mass ratio of chondroitin sulfate to dihydrazide is 1:2-10, preferably 1:2-5;

[0136] b) adjusting the pH to 3-6, mixing the mixed solution obtained in step a) with an activator to react;

[0137] c) adjusting the pH of the reaction solution obtained in step b) to 5-8 and then quenching; wherein quenching means placing the reaction solution in an ice bath at 0-5°C within 5 minutes and leaving it for 5-10 hours;

[0138] d) obtaining the aminated chondroitin sulfate by post-dialysis treatment.

[0139] In another preferred embodiment, the oxidized dextran is prepared by the following method, which comprises the following steps:

[0140] i) mixing dextran and an oxidant in water and reacting them in the dark, wherein the ratio of the dextran to the oxidant is 10-20 mol sugar unit: 1 mol, preferably 12-18 mol sugar unit: 1 mol;

[0141] ii) adding diethylene glycol to terminate the reaction;

[0142] iii) After dialysis, oxidized dextran is obtained.

[0143] Use of the injectable composite cross-linked structure of the present invention

[0144] The cross-linked structure of the present invention can be used for cartilage repair and treatment of osteoarthritis.

[0145] The cross-linked structure of the present invention has one or more of the following characteristics:

[0146] i) Reduced OARSI scores in osteoarthritis mice;

[0147] ii) reduction of synovial area and cartilage defect;

[0148] iii) reduce osteoclastogenesis;

[0149] iv) Reduced knee joint tissue damage and swelling in osteoarthritis mice;

[0150] v) Alleviate cartilage degeneration, cell apoptosis and aging.

[0151] The main advantages of the present invention are:

[0152] (1) The cross-linked structure of the present invention can be directly injected into the ideal location, thereby improving bioavailability and performing release therapy in a minimally invasive manner, with little impact on the patient;

[0153] (2) The cross-linked structure of the present invention cross-links the two cartilage nutrients, prolonging their respective retention time and achieving a sustained release effect;

[0154] (3) The preparation method of the cross-linked structure of the present invention is simple and low-cost;

[0155] (4) The cross-linked structure of the present invention can have excellent therapeutic effects without the need to add additional growth factors;

[0156] (5) The cross-linked structure of the present invention has excellent therapeutic effects, which can significantly reduce osteoclast formation (reduced by more than 45%), reduce knee joint cavity swelling (reduced by more than 30%), and reduce the OARSI score, synovial area and cartilage defect of osteoarthritis mice, thereby effectively treating osteoarthritis.

[0157] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods for the unrecorded specific conditions in the following examples are usually based on conventional conditions or the conditions recommended by the manufacturer. Unless otherwise stated, percentages and parts are weight percentages and weight parts.

[0158] Unless otherwise specified, the experimental materials and reagents used in the following examples can be obtained from commercial channels.

[0159] Example 1: Preparation of CS-ADH

[0160] Synthesis diagram Figure 1 As shown in a, chondroitin sulfate (CS), molecular weight 50-100 kDa, was purchased from Sangon Biotechnology Co., Ltd. (Shanghai). CS (1 g) and dihydrazide (4.4 g) were stirred and dissolved in 200 ml of water for 10 minutes. The pH of the solution was adjusted to 4.5 with 1M HCl solution, and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride (240 mg) and NHS were added. The reaction was continued at room temperature for 4 hours, and then the pH was adjusted to 7.0 with 1M NaOH solution and quenched. The reaction apparatus was placed in an ice water bath at 0 degrees and reacted for 6 hours. The solution was thoroughly dialyzed (MWCO 8000-14000) for 3 days under the conditions of 0.1M NaCl, 25% alcohol and water. The product was lyophilized and stored at 4°C for further use. The NMR data are shown in Figure 3 As shown in a.

[0161] It has been calculated that the grafting rate of chondroitin sulfate is between 55% and 72%.

[0162] Example 2. Synthesis of Oxidized Dextran (Odex)

[0163] The chemical structure of oxidized dextran (Odex) is as follows Figure 1 As shown in b, dextran (Dex), with an average molecular weight of 700 kDa, was purchased from Macklin. Dextran (1 g, 6 mmol sugar unit) and NaIO4 (90 mg, 20 mL) were dissolved in 100 ml of deionized water. The reaction was carried out in the dark at room temperature for 12 h. Then diethylene glycol (26 μL) was added to remove the unreacted NaIO4.

[0164] The mixture (MWCO 8000-14000) was dialyzed in 1 L of DI water for 3 days and freeze-dried to obtain Odex as a white powder. The NMR data are as follows: Figure 3 As shown in b.

[0165] It was calculated that the oxidation degree of oxidized dextran was about 4.4%.

[0166] Example 3. Preparation of a cross-linked structure of chondroitin sulfate and oxidized dextran (CS-Odex)

[0167] Schematic diagram as Figure 2 As shown, Odex and CS-ADH were first dissolved in PBS at concentrations of 5%, 4% and 3% (w / v), respectively.

[0168] The two pre-gel solutions were mixed in equal volumes to form three cross-linked structures, abbreviated as Gel 1 (5% Odex + 5% CS-ADH), Gel 2 (4% Odex + 4% CS-ADH), and Gel 3 (3% Odex + 3% CS-ADH).

[0169] Example 4 Physical characterization and identification of CS-Odex cross-linked structure

[0170] The morphology of the cross-linked structure after a thin layer of gold piles was coated and completely freeze-dried at an accelerating voltage of 15 kV was studied by scanning electron microscopy (SEM) (JCM-6000, JEOL, Japan). Figure 4 ).

[0171] The results show that a porous cross-linked structure is formed with a pore size between 20 and 100 μm. It can be seen that with the increase in the amount of CS-ADH and Odex added, the degree of cross-linking increases and the pore size in the cross-linked structure gradually becomes smaller.

[0172] To analyze the viscoelastic properties of the cross-linked structures, rheological tests were performed using a Physica MCR 501 rheometer (Anton Paar, Austria) with parallel plate geometry (25 mm diameter) and characterization based on storage modulus (G') and loss modulus (G''). The gap between the two plates was set to 1 mm. During the entire test, the test chamber was covered to avoid evaporation of water. After vigorous stirring, the mixture of CS and Odex was poured on the plate. The gel time was calculated using a time sweep test (1% strain, 1 Hz) and was defined as G' = G''.

[0173] The results are as follows Figure 5 As shown in b, the gelation time of the cross-linked structure of the present invention is about 10-50 minutes, among which Gel 1 has a short gelation time of only 10 minutes. The frequency sweep test is carried out in the range of 0.1-100 rad / s, and the cross-linked structure is formed at a strain of 1%.

[0174] In addition, strain amplitude sweep tests (0.1-100%, 1 Hz) were performed ( Figure 6 a), step strain test with alternating strains of 1% (low) and 100% (high) at 1 Hz frequency ( Figure 6 b).

[0175] The swelling properties of the CS-Odex cross-linked structure were studied as follows. The cross-linked structure was incubated in PBS at 37°C for 24 h to achieve swelling equilibrium. Then, the swollen cross-linked structure was wiped clean of the surface solution, weighed, and finally freeze-dried. The swelling ratio (SR) was calculated by the following formula, where Wt and W0 represent the mass of the swollen cross-linked structure and the dry cross-linked structure, respectively ( Figure 5 a).

[0176] The results show that the swelling ratio of Gel 3 with a concentration of 3% is the highest, exceeding 20%, and due to the effect of the cross-linked acylhydrazone bonds, the cross-linked structure only swells but does not dissolve when it comes into contact with water.

[0177] Example 5 Injectability and self-healing ability of CS-Odex cross-linked structure

[0178] The actual picture of the CS-Odex cross-linked structure vial tilting to form gel is as follows Figure 7 As shown in a.

[0179] The cross-linked structure formed by 5% CS+5% Odex dyed with methylene blue was placed in a syringe. After 5 minutes, it could be injected into water through a 3G needle, and the cross-linked structure remained stable ( Figure 7 b), The results show that the formed cross-linked structure can still be injected.

[0180] The cross-linked structure of the present invention is an injectable cross-linked structure, which can be directly injected into the lesion to improve the therapeutic effect. In addition, we can still inject the syringe into the joint cavity using an extremely fine injection needle, indicating that the flowability and injection performance of the CS-Odex cross-linked structure are excellent.

[0181] The self-healing behavior of the cross-linked structure was measured at a macroscopic scale using a mobile phone camera. First, a cross-linked structure formed by 5% CS + 5% Odex was used, and the cross-linked structure was cut into two halves, and stained with rhodamine B and methylene blue solution, respectively, to obtain a semicircular cross-linked structure that appeared blue and red, respectively. Then, the two semicircular cross-linked structures were put together for self-healing, and self-repair and self-healing were completed within 30 minutes ( Figure 7 c). Through staining, it can be clearly seen that the cross-linked structure undergoes self-healing behavior and has strong adhesion, indicating that the cross-linked structure of the present invention is suitable for treating cartilage degeneration caused by osteoarthritis.

[0182] Example 6 Ultrasonic detection of mouse knee joint

[0183] Forty-four clean-grade 10-week-old C57BL / 6J male mice were randomly divided into Sham group (n=16), PBS group (n=12) and Gel group (n=16) according to body weight. Each group was tested 8 and 12 weeks after knee surgery. For the PBS group and Gel group, knee osteoarthritis was induced by the destabilization of the medial meniscus (DMM) model of the knee joint. The mice were anesthetized with isoflurane before surgery, and meloxicam (2 mg / kg body weight) was injected subcutaneously to relieve pain. Each group of mice was injected with different drugs (PBS or Gel) every two weeks, and the Sham group was not injected. The mice were tested at 8 and 12 weeks after surgery. The volume of the knee joint cavity was calculated by 3D ultrasonic imaging of the mouse knee joint, and the degree of swelling of the mouse knee joint was evaluated.

[0184] A small animal ultrasound imager with three-dimensional function was used to set the parameters of the mouse knee joint. First, the mouse was anesthetized and fixed, and the test gel was applied to the surface of the mouse knee joint. The maximum sagittal plane area of ​​the mouse knee joint was measured with an ultrasound probe. Then the probe was adjusted left and right to determine the width of the knee joint and set the scan width. The scan width was set to 0.5-0.7cm, and 3D mode was used for scanning. In the experiment, isoflurane was used to maintain anesthesia for the mice. Vevo Lab 3.2.0 software was used for data analysis to obtain a three-dimensional image of the mouse knee joint cavity and its size, and to analyze the degree of knee joint swelling ( Figure 8 a).

[0185] There were significant differences between the surgical model groups (PBS group and Gel group) and the Sham group at week 8 (p<0.05). The PBS group showed obvious knee joint swelling and a significant increase in the cavity volume, while the swelling in the Gel group was reduced compared with the PBS group.

[0186] Similarly, at week 12, the knee joint cavity volume of the surgical model group mice was statistically significant compared with the Sham group, the knee joint swelling in the PBS group increased further, and the cavity volume was more than twice that of the Sham group, while the swelling in the Gel group was reduced by more than 30% compared with the PBS group. The KOA mice induced by the surgical model had larger knee joint cavities and joint swelling.

[0187] At 8 and 12 weeks after surgery, the joint cavity volume of the Gel group was smaller than that of the PBS group, indicating that intra-articular injection of CS-Odex cross-linked structure can reduce the knee joint cavity volume of KOA mice and alleviate joint swelling ( Figure 8 b).

[0188] Example 7 ABOG, type X collagen, and osteoclast staining of paraffin sections of mouse knee joints

[0189] Before surgery, mice were anesthetized with isoflurane and meloxicam (2 mg / kg body weight) was injected subcutaneously to relieve pain. Each group of mice was injected with different drugs every two weeks. The knee joints were tested and sampled 8 and 12 weeks after surgery. Paraffin specimens were made, 4 μm continuous sections were sliced, and alcian blue hematoxylin / orange G (ABOG) was used for tissue morphology staining. The articular cartilage area and synovial area were counted. The OARSI score was used to evaluate the joint structure morphology. Immunohistochemical staining was used to observe the expression of type X collagen in the knee joint and evaluate the degeneration of articular cartilage. Trap staining was used to count the number of osteoclasts.

[0190] ABOG staining: All knee joint specimens were fixed with 10% paraformaldehyde at room temperature for 48 hours and decalcified with 10% EDTA for 14 days. All knee joint specimens were paraffin-embedded and serially sectioned at 4 μm thickness. Twenty sections were selected from the knee joint to represent the entire joint and divided into three levels. Each layer differed from the previous layer by 28 μm. The three horizontal sections were stained with Alcian blue / orange G (ABOG).

[0191] Col X staining: Knee joint sections were pretreated in xylene to remove paraffin. Hydrogen peroxide was then added to the sections for 10 minutes to reduce the activity of endogenous peroxides. The sections were incubated with proteinase K for 10 minutes at 37°C to retrieve antigens, and then placed in 4% bovine serum albumin-phosphate buffered saline (BSA; BioFroxx, German; Cat. No: 4240GR100) for 1 hour to expose collagen antigen epitopes. Type X collagen antibody was diluted 1:1000 (ab58632, Abcam, UK) and incubated overnight at 4°C. After washing three times with 0.4% BSA / PBS, the sections were incubated with secondary antibodies (Goat Anti-Rabbit IgG (H+L) antibody, Vector Laboratories, BA-1000). Finally, sections were treated with a mixture of biotin and biotinylated horseradish peroxidase for color development on a peroxidase substrate (Vector Laboratories, Burlingame, CA 94010). Hematoxylin was used to counterstain sections. Negative controls were included by omitting the primary antibody to check for the appropriate specificity and performance of the applied reagents.

[0192] Trap staining: Place the dewaxed sections in 0.4 mg / ml naphthol ether solution / basic stock culture medium in a 37°C water bath for 30 min, then add 0.04 g / mL sodium nitrite solution and 0.05 g / mL pararosaniline dye / 2N hydrochloric acid solution and incubate for 15 min, and finally counterstain the sections with hematoxylin.

[0193] All images were analyzed using Olympus Olyvia software. Joint structure was scored using a semiquantitative scoring system designed by the Osteoarthritis Research Society International (OARSI) working group, with damage ranging from 0 (no damage) to 6 (complete cartilage stripping). For each knee analyzed, slides representing the entire joint were blinded and scored by two independent investigators. Regions of interest were demarcated by the software, including the distal femur, tibia, meniscus, articular cartilage, synovium, ligaments, and adjacent soft tissues. The total area was automatically calculated using Olympus VS-120 software.

[0194] Histological staining of paraffin sections of mouse knee joints ( Fig. 9 ) showed that the joint structure of the Sham group did not change significantly over time. Compared with the PBS model group, the PBS model group showed articular cartilage loss, subchondral bone destruction, meniscus injury, synovial hyperplasia, osteophyte formation and other manifestations. The cartilage indicated by the arrow in the figure was obviously missing, and the cartilage area was significantly reduced. OARSI scoring analysis of joint structure showed that with the progression of KOA, the joint structure was gradually destroyed. At 8 and 12 weeks, the knee cartilage area of ​​KOA model mice was significantly reduced.

[0195] By injecting CS-Odex cross-linked structures into the knee joints of mice, the area of ​​articular cartilage in the Gel group was improved compared with that in the PBS group at 12 weeks. CS-Odex effectively delayed the loss of articular cartilage and the destruction of joint structure 12 weeks after surgery. The cartilage indicated by the arrow in the figure showed a significant increase in cartilage area compared with the PBS, indicating that the Gel group can effectively improve the cartilage structure. In addition, the number of osteoclasts in the Gel group at 8 and 12 weeks was significantly lower than that in the PBS model group, and the difference was statistically significant.

[0196] The above studies show that KOA model mice have cartilage loss, synovial hyperplasia, and joint structure destruction at 8 and 12 weeks. Joint injection of CS-Odex cross-linked structure can significantly improve the joint structure of osteoarthritis and reduce joint degeneration ( Fig.10 ), especially osteoclast number which decreased by more than 45% within 12 weeks.

[0197] The specific data are shown in Table 1.

[0198] Table 1 Changes in cartilage area, synovial area, OARSI score, type X collagen positive area and osteoclast number in the sham group, PBS combination and Gel group at week 8 and 12

[0199]

[0200] All documents mentioned in the present invention are cited as references in this application, just as each document is cited as reference individually. In addition, it should be understood that after reading the above teachings of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

Claims

1. An injectable composite cross-linked structure, wherein the cross-linked structure is obtained by mixing and cross-linking an oxidized dextran solution and an ammoniated chondroitin sulfate solution; The oxidation degree of the oxidized dextran is below 10%; the amino grafting rate of the ammoniated chondroitin sulfate is 40%-80%.

2. The injectable composite cross-linked structure according to claim 1, characterized in that: The oxidation degree of the oxidized dextran is 1%-8%, more preferably 2%-5%; The amino grafting rate of the aminated chondroitin sulfate is 50-75%.

3. The injectable composite cross-linked structure according to claim 1, characterized in that: In the oxidized dextran solution, the concentration of oxidized dextran is 1%-10% (w / v); in the aminated chondroitin sulfate solution, the concentration of aminated chondroitin sulfate is 1%-10% (w / v).

4. The injectable composite cross-linked structure according to claim 1, characterized in that: The injectable composite cross-linked structure comprises one or more of the following features: (1) The aminated chondroitin sulfate is chondroitin sulfate grafted with dihydrazide; (2) The glucan is selected from the group consisting of dextran, β-glucan, or a combination thereof; (3) The molecular weight of the oxidized dextran is 4000-25000; (4) The molecular weight of the aminated chondroitin sulfate is 4000-25000.

5. The injectable composite cross-linked structure according to claim 1, characterized in that: The aminated chondroitin sulfate is prepared by the following method, which comprises the following steps: a) mixing chondroitin sulfate and dihydrazide in water, wherein the mass ratio of chondroitin sulfate to dihydrazide is 1:2-10, preferably 1:2-5; b) adjusting the pH to 3-6, mixing the mixed solution obtained in step a) with an activator to react; c) adjusting the pH of the reaction solution obtained in step b) to 5-8 and then quenching; wherein quenching means placing the reaction solution in an ice bath at 0-5°C within 5 minutes and leaving it for 5-10 hours; d) obtaining the aminated chondroitin sulfate by post-dialysis treatment.

6. The injectable composite cross-linked structure according to claim 1, characterized in that: The oxidized dextran is prepared by the following method, which comprises the following steps: i) mixing dextran and an oxidant in water and reacting them in the dark, wherein the ratio of the dextran to the oxidant is 10-20 mol sugar unit: 1 mol, preferably 12-18 mol sugar unit: 1 mol; ii) adding diethylene glycol to terminate the reaction; iii) After dialysis, oxidized dextran is obtained.

7. The injectable composite cross-linked structure according to claim 1, characterized in that: The injectable composite cross-linked structure is prepared by the following method, which comprises the steps of: (a) providing the oxidized dextran solution and the aminated chondroitin sulfate solution; (b) mixing the oxidized dextran solution and the aminated chondroitin sulfate solution, and cross-linking them to obtain a composite cross-linked structure.

8. The method for preparing an injectable composite cross-linked structure according to claim 1, characterized in that: Includes steps: (a) providing the oxidized dextran solution and the aminated chondroitin sulfate solution; (b) mixing the oxidized dextran solution and the aminated chondroitin sulfate solution to obtain a composite cross-linked structure.

9. Use of the injectable composite cross-linked structure according to claim 1 in preparing a pharmaceutical composition for preventing and / or treating osteoarthritis.

10. A composition or preparation, characterized in that The composition or formulation comprises: a) the injectable composite cross-linked structure according to claim 1, and b) a pharmaceutically and / or nutraceutically acceptable carrier.